Analysis of risk factors for pre-diabetes to diabetes among cadres in Huzhou: a 5-year retrospective study: Risk factors for pre-diabetes to diabetes - Wu, Yan; Yao, Jun; Xing, Shitong; Zhang, Ying; Shen, Yan (Journal of Medical Biochemistry, 2025)
Objective To analyze the risk factors of Diabetes Mellitus (DM) through a five-year retrospective study of prediabetes mellitus (Pre DM) cadres. Methods The cadres who underwent physical examination and were diagnosed as pre-diabetes in the First People's Hospital of Huzhou City from April 2019 to November 2024 were selected as the research objects, and their basic information (age, gender, body mass index, etc.), lifestyle (diet, exercise, smoking and drinking, etc.), family medical history, biochemical indicators (blood sugar, blood lipid, blood pressure, etc.) and other data were collected. People were divided into two groups according to whether they developed diabetes, and the risk factors of diabetes were determined by univariate analysis and multivariate Logistic regression analysis. Results A total of 174 pre-diabetic cadres were included, and 30 of them developed diabetes. Univariate analysis showed that there were differences in age, body mass index, fasting blood glucose, triglyceride, uric acid, blood pressure, blood lipid, liver function and lack of exercise of renal function between the two groups (P < 0.05). The results of multivariate Logistic regression analysis showed that age, BMI, SBP, TG, TC, BUN, TBIL and ALT were independent risk factors for the development of diabetes in pre-diabetic cadres' health care population within 5 years (P < 0.05). Conclusion This study shows that age, BMI, blood pressure, blood lipid level, liver and kidney function indexes and gender are important risk factors for PDM patients to develop into DM. Monitoring and managing these factors can reduce the risk of PDM patients progressing to DM. This provides personalized health management suggestions for PDM cadres and health care people, and also provides theoretical support for the formulation of relevant health policies.
Keywords: diabetes; Pre-diabetes; Cadres' health care population; Risk factors